(untitled) (Al-Academy, 2017)
Observed mosques with the advent of Islam under the auspices of care being the houses of God Almighty, and I like parts of the ground to him, the center of radiation spiritual, intellectual and ideological in the lives of Muslims, was the most important cultural and architectural evidence built by Muslims voicing their deep faith and serenity Aqidthm.valmsadjad better reflecting the reality of communication between the person and his Lord, because he is the most important building of permanence and survival, making it imperative designed the best visual forms both externally and internally.Mosques have been characterized in the United Arab Emirates distinct characteristics in terms of building elements of construction in general, and the mechanism of evolution of the inner core vocabulary particular, note that the development of the internal design architecture of the mosques in the emirate of Sharjah was one of the top priorities of the Department of Islamic Affairs and Awqaf in the emirate in terms of the safety of the visual forms and free from the alienation of the intellectual concepts of those mosques, especially those design wizards implemented in the interior spaces of the mosques, so the problem of current research emanating from the importance of the evolutionary structure of the concept of interior design of mosques in Sharjah, as evolution inevitability of the concept of interior design movement and that the latter part of human knowledge and growth, and the lack of studies precedent in this area and because some previous studies and attempts have paid great attention mesh mosques in terms of form and meaning, and not to their access to the internal space Adoua and sophisticated, so the current research aims to achieve the following goals:1 -akoshv theoretical to the reality of the interior design of mosques in Sharjah in terms of configuration the formal vocabulary of building space to the mosque from the inside.2 - Detection Applied to the physical data for the development of the mosques in the United Arab Emirates in general and Sharjah in particular